A high-strength degradable aluminum alloy material and a preparation method thereof

By adding specific elements to aluminum alloys to form low-melting-point eutectic phases and micro-galvanic cells, and combining this with heat treatment technology, the problems of uncontrollable dissolution rate and low strength of aluminum alloys under high temperature and high pressure conditions have been solved. A biodegradable aluminum alloy with good dissolution performance and high strength at 90℃ has been prepared, which is suitable for fracturing tools for tight gas and shale gas extraction.

CN120425208BActive Publication Date: 2025-12-05SHANXI RUIGE ZHONGBEI LIGHT METAL NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510633576.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-12-05
Estimated Expiration
2045-05-16

AI Technical Summary

Technical Problem

Existing soluble aluminum alloys have uncontrollable dissolution rates and low strength under high temperature and high pressure conditions, which cannot meet the needs of tight gas and shale gas extraction.

Method used

By adding elements such as Zn, Cu, Zr, Ga, In, Sn, Li, V, and Hf to aluminum alloys, low-melting-point eutectic phases and microscopic galvanic cells are formed, promoting oxide film rupture and activation dissolution. Combined with heat treatment technology, the microstructure is optimized, thereby improving the strength and dissolution rate of the alloy.

Benefits of technology

The prepared high-strength biodegradable aluminum alloy has a dissolution rate of 120-195 mg/cm²/h at 90℃, a tensile strength of 332 MPa, and a yield strength of 264 MPa, meeting the requirements for fracturing tools in unconventional natural gas extraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120425208B_ABST
    Figure CN120425208B_ABST
Patent Text Reader

Abstract

The application discloses a high-strength degradable aluminum alloy material and a preparation method thereof, and relates to the field of non-ferrous metal alloy preparation.The high-strength degradable aluminum alloy material comprises the following components in percentage by weight: Zn 3.0-7.0%, Cu 0.5-1.5%, Zr 0.05-0.35%, Ga 0.1-4.0%, In 0.1-2.0%, Sn 0.1-4.0%, Li 0.001-1.5%, V 0.005-0.05%, Hf 0.005-0.05%, the rest being Al and inevitable impurities, wherein the content of the impurities is less than or equal to 0.2%, the mass ratio of Ga and In is 2-3, and the mass ratio of Sn and In is 1-2.The high-strength degradable aluminum alloy material is prepared through the steps of smelting treatment, alloy casting, extrusion forming and heat treatment, and has the advantages that the high-strength degradable aluminum alloy material provided by the application is a soluble aluminum alloy material, the tensile strength at room temperature can reach 332 MPa, the yield strength can reach 264 MPa, the dissolution rate in a 90 DEG C, 3wt% KCl solution is 120-195 mg / cm 2 / h, and the mechanical properties are excellent, so that the high-strength degradable aluminum alloy material can be applied to deep well mining and other high-demand fracturing environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of non-ferrous metal alloy preparation technology, and particularly relates to a high-strength biodegradable aluminum alloy material and its preparation method. Background Technology

[0002] Conventional natural gas resources have been gradually depleted after long-term exploitation, leading to increased attention being paid to unconventional natural gas resources such as tight gas and shale gas. Tight gas and shale gas resources are widely distributed in my country, with most domestic shale gas buried deep within hard rock. These resources are characterized by very low matrix permeability, making horizontal well fracturing technology a crucial means to effectively increase the production of unconventional energy. Traditional downhole fracturing tools are made of drillable ductile iron, which, while possessing high mechanical properties, still presents some challenges, such as the need for drilling and removal after fracturing. The application of soluble fracturing plugging tools has significantly improved extraction efficiency, eliminating the need for drilling and removal processes and greatly reducing costs. Therefore, the development of soluble alloys has attracted considerable attention within the industry.

[0003] Based on the working environment and technical requirements of soluble fracturing balls (certain high-temperature resistance, high tensile strength, low density, good machinability, and matched galvanic corrosion resistance), aluminum alloy materials possess comprehensive properties such as high strength, low density, and high-temperature resistance, and are widely used in aerospace, defense, and other fields. Soluble aluminum alloys are mainly developed and applied by adding low-melting-point metals such as Ga, In, and Sn to improve the alloy's solubility. Currently, the biodegradable materials developed and applied in the market mainly include biodegradable resins, soluble magnesium alloys, and soluble aluminum alloys. However, biodegradable resins cannot meet the requirements of high-temperature and high-pressure environments, and soluble magnesium alloys have low strength and complex manufacturing processes, making them unsuitable for the special working environments such as downhole fracturing in oil and gas wells.

[0004] Aluminum alloys possess advantages such as low reactivity, significantly higher strength than magnesium alloys, relatively safer production, and simpler processes. Chinese patent (patent number 202310460453.1) discloses a biodegradable thermosetting composite material and a biodegradable downhole plugging tool prepared from it. This method prepares the thermosetting composite material by combining high glass transition temperature epoxy resin and low glass transition temperature epoxy resin, but the material's strength is only 82.74 MPa. Chinese patent (patent number 202210404063.8) discloses a high-ductility soluble aluminum alloy based on an Al-Mg alloy system, using low-content Ga, In, and Sn as additives. The Al-Mg-Ga-In-Sn alloy system is prepared through a melting and casting method, and its mechanical properties are improved through hot extrusion and heat treatment. This invention only reports the dissolution rate at room temperature. Since the extraction temperature of unconventional natural gas typically exceeds 90°C, the alloy needs to withstand temperatures above 90°C. Chinese patent (patent number 202410101865.0) reports a high-strength soluble magnesium alloy in which the content of light rare earth elements and heavy rare earth elements reaches 9.2% to 13.0%, which greatly increases the production cost. Because magnesium has high activity and relatively low strength compared to aluminum, it poses a significant safety hazard in production and is not suitable for large-scale industrial production of fracturing tools. Summary of the Invention

[0005] To address the problems of uncontrollable dissolution rate and low strength in existing soluble aluminum alloys, this invention proposes a high-strength biodegradable aluminum alloy material and its preparation method. The high-strength biodegradable aluminum alloy material prepared by this invention has good mechanical properties and biodegradability, and is low in cost and high in strength.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] One of the technical solutions of the present invention:

[0008] This invention provides a high-strength biodegradable aluminum alloy material, comprising the following components by weight percentage: Zn 3.0–7.0%, Cu 0.5–1.5%, Zr 0.05–0.35%, Ga 0.1–4.0%, In 0.1–2.0%, Sn 0.1–4.0%, Li 0.001–1.5%, V 0.005–0.05%, Hf 0.005–0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%, and the mass ratio of Ga to In is 2–3, and the mass ratio of Sn to In is 1–2.

[0009] This invention redesigns and controls the composition of Al-Zn alloys. By adjusting the ratio of Ga, In, Sn, and Li, low-melting-point eutectic phases such as In3Sn, Al2CuLi, and Ga-In3Sn-InSn4 are formed at the grain boundaries. Al atoms can dissolve into the eutectic alloy and become active sites in the dissolution process, hindering and destroying the oxide film on the alloy surface. The high-strength biodegradable aluminum alloy material provided by this invention has a dissolution rate of 120–195 mg / cm³ in a 3 wt% KCl solution at 90°C. 2 The high-strength biodegradable aluminum alloy material provided by this invention exhibits good biodegradability. Its tensile strength can reach 332 MPa, and its yield strength can reach 264 MPa.

[0010] Zn is the main alloying element in soluble aluminum alloys. When the Zn content is between 0.5% and 5%, the alloy potential decreases by 0.22V. With increasing Zn content, the formation of ZnAl2O4 spinel is promoted. Since the molar volume of ZnAl2O4 spinel is larger than that of the Al2O3 oxide film, and excess Zn accumulates between the aluminum matrix and the Al2O3 oxide film, it leads to the rupture of the Al2O3 oxide film, thus increasing the alloy activity. Cu can increase the dispersion of precipitated phases in aluminum alloys. As a cathode metal, Cu forms a micro-galvanic cell with Al, accelerating alloy dissolution. In has very low solubility in Al, mainly existing in the form of segregated phases and solid solutions. The segregated phase formed with the Al matrix is ​​the main factor in the activation and dissolution of aluminum-based soluble alloys. An In-rich layer is formed between the matrix and the metal surface oxide film, effectively destroying the Al surface oxide film, reducing the density of the alloy surface oxide film, and promoting the formation and expansion of pitting corrosion on the alloy surface. Simultaneously, the In in the solution... 3+Ions deposit on the Al surface through a displacement reaction, thus continuing activation. In different solution environments, controlling the In content can allow the material to achieve different dissolution rates. Sn exists as single or multiple atoms at grain boundaries in aluminum-based soluble alloys, forming an alloy phase embedded in the oxide film on the aluminum matrix surface. Simultaneously, it forms activation sites to separate or destroy the oxide film on the matrix surface, thereby playing an activation role. Ga, due to its low melting point (29.76℃), readily forms low-melting-point compounds with other alloying elements. When the temperature rises, Ga deposits in liquid form on the aluminum matrix surface, forming an amalgam-like Al-Ga liquid metal with Al, separating the matrix and oxide film. This creates numerous active sites on the aluminum matrix surface. As the number of active sites increases, the exposed aluminum matrix is ​​gradually activated and dissolved. In Al-Ga alloys, the activation of Al by Ga is not an instantaneous process; therefore, the dissolution rate can be controlled by adjusting the Ga content. Zr acts as a grain refiner and strengthens the material, playing a crucial role in improving its strength. Heat treatment induces the precipitation of dispersed Al3Zr particles, and dispersion strengthening significantly improves the strength and toughness of the alloy. Trace element V enhances the tensile strength and elongation of the aluminum alloy. Trace amounts of Hf can form a high-temperature stable compound, Al3Hf, with aluminum, further improving the alloy's heat resistance and acting as nucleation sites to enhance the alloy's heterogeneous nucleation ability, resulting in a certain degree of refinement of the alloy microstructure.

[0011] Preferably, the high-strength biodegradable aluminum alloy material comprises, by weight percentage, the following components: Zn 5.0–7.0%, Cu 0.5–1.2%, Zr 0.2–0.3%, Ga 1.0–3.0%, In 0.4–1.0%, Sn 1.0–1.5%, Li 0.05–1.2%, V 0.01–0.05%, Hf 0.01–0.035%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%, and the mass ratio of Ga to In is 2–3, and the mass ratio of Sn to In is 1–2.

[0012] As another preferred embodiment, the high-strength biodegradable aluminum alloy material comprises, by weight percentage, the following components: Zn 3.0–5.0%, Cu 1.0–1.5%, Zr 0.25–0.35%, Ga 2.5–4.0%, In 1.5–2.0%, Sn 1.5–4.0%, Li 0.8–1.5%, V 0.01–0.05%, Hf 0.01–0.035%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%, and the mass ratio of Ga to In is 2–3, and the mass ratio of Sn to In is 1–2.

[0013] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 7%, Cu 0.5%, Zr 0.24%, Ga 1.8%, In 0.8%, Sn 1.5%, Li 0.05%, V 0.02%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0014] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 7%, Cu 1.2%, Zr 0.2%, Ga 1.2%, In 0.5%, Sn 1%, Li 0.3%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0015] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 6%, Cu 0.8%, Zr 0.3%, Ga 1%, In 0.5%, Sn 1%, Li 0.8%, V 0.03%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0016] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 6%, Cu 1.2%, Zr 0.15%, Ga 2.5%, In 1%, Sn 1%, Li 0.4%, V 0.05%, Hf 0.02%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0017] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 5%, Cu 1.2%, Zr 0.3%, Ga 3%, In 1%, Sn 1.5%, Li 1.2%, V 0.02%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0018] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 4%, Cu 1.5%, Zr 0.25%, Ga 3%, In 1.5%, Sn 1.5%, Li 0.8%, V 0.05%, Hf 0.04%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0019] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 3%, Cu 0.8%, Zr 0.26%, Ga 3%, In 1%, Sn 1%, Li 1.5%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0020] For example, the high-strength biodegradable aluminum alloy material is composed of the following components by weight percentage: Zn 3%, Cu 0.5%, Zr 0.05%, Ga 4%, In 2%, Sn 4%, Li 1.2%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0021] The second technical solution of the present invention:

[0022] This invention also provides a method for preparing the above-mentioned high-strength biodegradable aluminum alloy material, comprising the following steps:

[0023] Under inert gas protection, pure aluminum ingots are heated and melted to obtain molten aluminum. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added to the molten aluminum and stirred thoroughly. After refining and degassing, the mixture is allowed to stand and then cast into a semi-continuous casting rod.

[0024] The semi-continuous casting rod is subjected to homogenization treatment;

[0025] The homogenized semi-continuous cast rod is subjected to hot extrusion to obtain the rod material.

[0026] The bar is heat-treated to obtain the high-strength biodegradable aluminum alloy material.

[0027] For example, the inert gas includes an argon or nitrogen atmosphere.

[0028] Zn, Ga, In, and Sn are added in pure metal form, while Cu, V, Zr, Hf, and Li are added in intermediate alloy form.

[0029] Furthermore, the refining process involves refining at 750–780°C for 10–30 minutes.

[0030] And / or, the degassing time is 10 to 20 minutes;

[0031] And / or, the settling time is 5 to 20 minutes.

[0032] Furthermore, a refining agent is added during the refining process.

[0033] The refining agent is a mixture of KCl, NaCl, Na3AlF6 and Na2CO3.

[0034] Furthermore, the homogenization treatment is carried out at a temperature of 440–470°C for a time of 10–20 hours.

[0035] Furthermore, during the hot extrusion process: the extrusion cylinder temperature is 380–460°C, the casting rod temperature is 400–500°C, the extrusion speed is 0.4–1.5 mm / s, and the extrusion ratio is 20–50.

[0036] Furthermore, the heat treatment includes solution treatment and aging treatment.

[0037] Furthermore, the solution treatment temperature is 450–500°C, and the solution treatment time is 0.5–2 hours;

[0038] And / or, the aging treatment temperature is 100-150℃, and the aging treatment time is 8-20h.

[0039] The third technical solution of the present invention:

[0040] The present invention also provides the application of the high-strength biodegradable aluminum alloy material in the preparation of fracturing tools for unconventional natural gas extraction.

[0041] For example, the unconventional natural gas includes tight gas or shale gas.

[0042] Compared with the prior art, the present invention has the following advantages and technical effects:

[0043] This invention forms a second-phase compound rich in low-melting-point metals on the surface of an aluminum matrix by adding a certain proportion of low-melting-point elements (Ga, In, Sn, and Li). Sn selectively accumulates at grain boundaries, forming an Al-Sn low-melting-point eutectic layer, significantly refining the grain boundary structure. Simultaneously, Sn and In synergistically form an Al-In-Sn ternary metastable phase, enhancing grain boundary corrosion susceptibility. During aging, Li preferentially reacts with Al to form Al3Li precipitates, providing a dislocation pinning effect and achieving precipitation strengthening. Furthermore, Li's high reactivity accelerates the rupture of the surface oxide film, forming a "self-catalytic" degradation channel. Ga, In, Sn, and Li form a gradient solid solution-segregation structure due to their varying solid solubility, inducing non-equilibrium dendrites during solidification and enhancing electrochemical heterogeneity at grain boundaries. The dissolution characteristics of this alloy stem from the synergistic effect of multiple elements: low-melting-point metals disrupt the passivation film and promote localized corrosion; Cu / Li exacerbates the galvanic effect and hydrogen embrittlement; and Zn acts as a sacrificial anode, accelerating overall corrosion. By optimizing the composition and controlling the microstructure, corrosion controllability can be improved while ensuring solubility, thus meeting the requirements of unconventional energy engineering technologies such as tight gas and shale gas. Attached Figure Description

[0044] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0045] Figure 1 This is a SEM image of the high-strength biodegradable aluminum alloy material in Example 2;

[0046] Figure 2 In Figure a, we see a physical image of the newly prepared high-strength biodegradable aluminum alloy material in Example 2, and in Figure b, we see a physical image of the material after degradation. Detailed Implementation

[0047] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0048] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0049] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0050] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0051] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0052] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage, the following components: Zn 3.0–7.0%, Cu 0.5–1.5%, Zr 0.05–0.35%, Ga 0.1–4.0%, In 0.1–2.0%, Sn 0.1–4.0%, Li 0.001–1.5%, V 0.005–0.05%, Hf 0.005–0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%, and the mass ratio of Ga to In is 2–3, and the mass ratio of Sn to In is 1–2.

[0053] Zn is the main alloying element in soluble aluminum alloys. When the Zn content is between 0.5% and 5 wt%, the corrosion potential of the alloy decreases by 0.22 V. With increasing Zn content, the formation of ZnAl2O4 spinel is promoted. Since the molar volume of ZnAl2O4 spinel is larger than that of the Al2O3 oxide film, and excess Zn accumulates between the aluminum matrix and the Al2O3 oxide film, it leads to the rupture of the Al2O3 oxide film, thus increasing the alloy activity. Cu can increase the dispersion of precipitated phases in aluminum alloys. As a cathode metal, Cu forms a micro-galvanic cell with Al, which can accelerate alloy dissolution. In has very low solubility in Al, mainly existing in the form of segregated phases and solid solutions. The segregated phase formed with the Al matrix is ​​the main factor in the activation and dissolution of aluminum-based soluble alloys. An In-rich layer is formed between the matrix and the metal surface oxide film, which can effectively destroy the Al surface oxide film, reduce the density of the alloy surface oxide film, and promote the formation and expansion of pitting corrosion on the alloy surface. Simultaneously, the In in the solution... 3+Ions deposit on the Al surface through electrochemical displacement reactions, forming an In-rich layer, thus allowing the activation reaction to continue. In different solution environments, controlling the In content can allow the material to achieve different dissolution rates. Sn exists as single or multiple atoms at grain boundaries in aluminum-based soluble alloys, forming an alloy phase embedded in the oxide film on the aluminum matrix surface. Simultaneously, it forms activation sites to separate or destroy the oxide film on the matrix surface, thereby playing an activation role. Ga, due to its low melting point (29.76℃), readily forms low-melting-point compounds with other alloying elements. When the temperature rises, Ga deposits in liquid form on the aluminum matrix surface, forming an Al-Ga liquid metal similar to an amalgam with Al, separating the matrix and oxide film. This creates numerous active sites on the aluminum matrix surface. As the number of active sites increases, the exposed aluminum matrix is ​​gradually activated and dissolved. In Al-Ga alloys, the activation of Al by Ga is not an instantaneous process; therefore, the dissolution rate can be controlled by adjusting the Ga content. Zr plays a grain-refining and strengthening role, crucially contributing to improving the material's strength. Heat treatment induces the precipitation of dispersed Al3Zr particles, and dispersion strengthening significantly improves the strength and toughness of the alloy. Trace element V enhances the tensile strength and elongation of the aluminum alloy. Trace amounts of Hf can form a high-temperature stable compound, Al3Hf, with aluminum, further improving the alloy's heat resistance and acting as nucleation sites to enhance the alloy's heterogeneous nucleation ability, resulting in a certain degree of refinement of the alloy microstructure.

[0054] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage, the following components: Zn 5.0–7.0%, Cu 0.5–1.2%, Zr 0.2–0.3%, Ga 1.0–3.0%, In 0.4–1.0%, Sn 1.0–1.5%, Li 0.05–1.2%, V 0.01–0.05%, Hf 0.01–0.035%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%, and the mass ratio of Ga to In is 2–3, and the mass ratio of Sn to In is 1–2.

[0055] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage, the following components: Zn 3.0–5.0%, Cu 1.0–1.5%, Zr 0.25–0.35%, Ga 2.5–4.0%, In 1.5–2.0%, Sn 1.5–4.0%, Li 0.8–1.5%, V 0.01–0.05%, Hf 0.01–0.035%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%, and the mass ratio of Ga to In is 2–3, and the mass ratio of Sn to In is 1–2.

[0056] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 7%, Cu 0.5%, Zr 0.24%, Ga 1.8%, In 0.8%, Sn 1.5%, Li 0.05%, V 0.02%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0057] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 7%, Cu 1.2%, Zr 0.2%, Ga 1.2%, In 0.5%, Sn 1%, Li 0.3%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0058] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 6%, Cu 0.8%, Zr 0.3%, Ga 1%, In 0.5%, Sn 1%, Li 0.8%, V 0.03%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0059] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 6%, Cu 1.2%, Zr 0.15%, Ga 2.5%, In 1%, Sn 1%, Li 0.4%, V 0.05%, Hf 0.02%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0060] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 5%, Cu 1.2%, Zr 0.3%, Ga 3%, In 1%, Sn 1.5%, Li 1.2%, V 0.02%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0061] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 4%, Cu 1.5%, Zr 0.25%, Ga 3%, In 1.5%, Sn 1.5%, Li 0.8%, V 0.05%, Hf 0.04%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0062] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 3%, Cu 0.8%, Zr 0.26%, Ga 3%, In 1%, Sn 1%, Li 1.5%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0063] In some embodiments of the present invention, the high-strength biodegradable aluminum alloy material comprises, by weight percentage: Zn 3%, Cu 0.5%, Zr 0.05%, Ga 4%, In 2%, Sn 4%, Li 1.2%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0064] Some embodiments of the present invention also provide a method for preparing the above-mentioned high-strength biodegradable aluminum alloy material, comprising the following steps:

[0065] Under inert gas protection, pure aluminum ingots are heated and melted to obtain molten aluminum. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added to the molten aluminum and stirred thoroughly. A refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in a mass ratio of 1:1:1:1) is added. The mixture is refined at 750-780℃ for 10-30 minutes, degassed for 10-20 minutes, allowed to stand for 5-20 minutes, and then cast into a semi-continuous casting rod.

[0066] The semi-continuous casting rod is homogenized: the homogenization temperature is 440-470℃ and the time is 10-20h;

[0067] The semi-continuous cast rod after homogenization is subjected to hot extrusion to obtain the rod. During the hot extrusion process, the extrusion barrel temperature is 380-460℃, the cast rod temperature is 400-500℃, the extrusion speed is 0.4-1.5mm / s, and the extrusion ratio is 20-50.

[0068] The bar stock is heat-treated to obtain a high-strength biodegradable aluminum alloy material. The heat treatment includes solution treatment and aging treatment. The solution treatment temperature is 450-500℃ and the solution treatment time is 0.5-2h. The aging treatment temperature is 100-150℃ and the aging treatment time is 8-20h.

[0069] For example, the inert gas includes an argon or nitrogen atmosphere.

[0070] In the following embodiments of the present invention, Zn, Ga, In and Sn are added in pure metal form, and Cu, V, Zr, Hf and Li are added in the form of intermediate alloys (AlCu50 alloy, AlV5 alloy, AlZr5 alloy, AlHf5 alloy, AlLi5 alloy).

[0071] This invention prepares high-strength biodegradable aluminum alloy materials through steps such as smelting, alloy casting, extrusion forming, and heat treatment. The high-strength biodegradable aluminum alloy material provided by this invention is a soluble aluminum alloy material with a room temperature tensile strength of up to 332 MPa and a yield strength of up to 264 MPa. Its dissolution rate in a 3 wt% KCl solution at 90°C is 120–195 mg / cm³. 2 / h, with excellent mechanical properties, can adapt to the high-requirement fracturing environment such as deep well mining.

[0072] The high-strength, biodegradable aluminum alloy material provided in this invention can be used to manufacture fracturing tools for unconventional natural gas extraction. For example, unconventional natural gas includes tight gas or shale gas.

[0073] Unless otherwise specified, the room temperature in this invention is 25±2℃.

[0074] All raw materials used in the embodiments of this invention were obtained through commercial purchase.

[0075] In the following embodiments and comparative examples of the present invention, the tensile strength and yield strength of the aluminum alloy materials were tested in accordance with GB / T228.1-2021;

[0076] The dissolution rate test method is as follows: Before the test, the molten sample is cut into φ30mm*20mm pieces. Then, the surface of the circular sample is coarsely ground and finely ground with 500#~7000# wet sandpaper until the sample surface is smooth and without any defects. Next, the sample is cleaned by ultrasonic vibration with acetone and anhydrous ethanol in sequence to remove impurities, oil stains and residual acetone from the sample surface. Finally, the sample is quickly dried with a hair dryer and wrapped with plastic wrap for later use to avoid recontamination. The initial weight of the sample was weighed using an analytical balance, and the relevant data was recorded. A 3.5 wt% KCl solution was prepared as the immersion environment according to the operating conditions. Next, the prepared KCl solution was filled into a beaker and placed in a constant temperature water bath to be heated to the set temperature (90℃). The sample was removed periodically, and according to the standard GB / T 16545-2015 "Removal of Corrosion Products from Metal and Alloy Corrosion Samples", the sample was washed in a 1.42 g / mL HNO3 solution for 2 minutes to remove the dissolved products on the surface. The sample surface was then washed with anhydrous ethanol and dried with a cold air blower. Finally, the remaining mass of the sample was weighed and recorded, and the weight loss rate was calculated. To ensure the accuracy of the test, three parallel samples of the same composition were selected for testing at the same temperature. Samples were taken every 12 hours, for a total of 12–15 samplings, and the average value was taken as the final solubility test result.

[0077]

[0078] V: Material dissolution rate (mg / (h*cm)) 2 ));

[0079] Mo: Mass of the sample before dissolution (mg);

[0080] Mt: Mass (mg) of the sample after t hours of surface dissolution products removal;

[0081] S: Represents the surface area (cm²) of the sample exposed to the environment. 2 );

[0082] t: Dissolution time (h).

[0083] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0084] The technical solution of the present invention will be further illustrated by the following embodiments.

[0085] Example 1

[0086] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 7%, Cu 0.5%, Zr 0.24%, Ga 1.8%, In 0.8%, Sn 1.5%, Li 0.05%, V 0.02%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0087] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0088] (1) Alloy smelting: Pure aluminum ingots are heated and melted under an argon atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 780℃ for 15 min, degassed for 10 min, and then allowed to stand for 5 min after slag removal to obtain the melt.

[0089] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 130 mm / min.

[0090] (3) Homogenization treatment: The homogenization temperature was 440℃ and the homogenization time was 15h;

[0091] (4) Extrusion forming (hot extrusion treatment): The homogenized soluble aluminum alloy casting is hot extruded. The extrusion barrel temperature is 400℃, the casting temperature is 420℃, the extrusion speed is 0.5mm / s, and the extrusion ratio is 20, to obtain... Soluble aluminum alloy extrusions;

[0092] (5) Heat treatment: The soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 480℃ and the solution time is 1h. The aging temperature is 110℃ and the aging time is 15h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0093] Example 2

[0094] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 7%, Cu 1.2%, Zr 0.2%, Ga 1.2%, In 0.5%, Sn 1%, Li 0.3%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0095] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0096] (1) Alloy smelting: Pure aluminum ingots are heated and melted under an argon atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 760℃ for 15 min, degassed for 15 min, and slag removed. After standing for 10 min, the melt is obtained.

[0097] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 150 mm / min.

[0098] (3) Homogenization treatment: The homogenization temperature was 470℃ and the homogenization time was 10h;

[0099] (4) Extrusion forming: The homogenized soluble aluminum alloy casting rod is hot-extruded. The extrusion barrel temperature is 420℃, the casting rod temperature is 480℃, the extrusion speed is 0.8mm / s, and the extrusion ratio is 40, to obtain... Soluble aluminum alloy extrusions;

[0100] (5) Heat treatment: The prepared soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 480℃ and the solution time is 1.5h. The aging temperature is 120℃ and the aging time is 15h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0101] The SEM image of the high-strength biodegradable aluminum alloy material in this embodiment is as follows: Figure 1 As shown, low-melting-point metals such as Ga, Sn, and In are enriched at the grain boundaries to form low-melting-point eutectic phases, which destroy the oxide film and promote localized corrosion.

[0102] The degradation effect (i.e., the dissolution rate) of the high-strength biodegradable aluminum alloy material prepared in this embodiment was tested. A photograph of the newly prepared high-strength biodegradable aluminum alloy material is shown below. Figure 2 As shown in Figure a, the actual image of the sample after 3 hours of degradation is as follows. Figure 2 As shown in Figure b, the high-strength biodegradable aluminum alloy material prepared by this invention has a good degradation effect.

[0103] Example 3

[0104] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 6%, Cu 0.8%, Zr 0.3%, Ga 1%, In 0.5%, Sn 1%, Li 0.8%, V 0.03%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0105] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0106] (1) Alloy smelting: Pure aluminum ingots are heated and melted under a nitrogen atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 775℃ for 20 min, degassed for 20 min, and then allowed to stand for 10 min after slag removal to obtain the melt.

[0107] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 120 mm / min.

[0108] (3) Homogenization treatment: The homogenization temperature is 450℃ and the homogenization time is 20h.

[0109] (4) Extrusion forming: The homogenized soluble aluminum alloy casting rod is hot-extruded. The extrusion barrel temperature is 380℃, the casting rod temperature is 460℃, the extrusion speed is 1.2mm / s, and the extrusion ratio is 50, to obtain... Soluble aluminum alloy extrusions.

[0110] (5) Heat treatment: The prepared soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 450℃ and the solution time is 2h. The aging temperature is 100℃ and the aging time is 20h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0111] Example 4

[0112] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 6%, Cu 1.2%, Zr 0.15%, Ga 2.5%, In 1%, Sn 1%, Li 0.4%, V 0.05%, Hf 0.02%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0113] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0114] (1) Alloy smelting: Pure aluminum ingots are heated and melted under a nitrogen atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 760℃ for 20 min, degassed for 15 min, and then allowed to stand for 15 min after slag removal to obtain the melt.

[0115] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 130 mm / min.

[0116] (3) Homogenization treatment: The homogenization temperature is 460℃ and the homogenization time is 12h;

[0117] (4) Extrusion forming: The homogenized soluble aluminum alloy casting rod is hot-extruded. The extrusion barrel temperature is 470℃, the casting rod temperature is 500℃, the extrusion speed is 1mm / s, and the extrusion ratio is 50, to obtain... Soluble aluminum alloy extrusions;

[0118] (5) Heat treatment: The prepared soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 490℃ and the solution time is 0.5h. The aging temperature is 150℃ and the aging time is 8h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0119] Example 5

[0120] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 5%, Cu 1.2%, Zr 0.3%, Ga 3%, In 1%, Sn 1.5%, Li 1.2%, V 0.02%, Hf 0.05%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0121] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0122] (1) Alloy smelting: Pure aluminum ingots are heated and melted under an argon atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 760℃ for 30 min, degassed for 10 min, and then allowed to stand for 20 min after slag removal to obtain the melt.

[0123] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 130 mm / min.

[0124] (3) Homogenization treatment: The homogenization temperature was 440℃ and the homogenization time was 15h;

[0125] (4) Extrusion forming: The homogenized soluble aluminum alloy casting rod is hot-extruded. The extrusion barrel temperature is 420℃, the casting rod temperature is 460℃, the extrusion speed is 0.4mm / s, and the extrusion ratio is 35, to obtain... Soluble aluminum alloy extrusions;

[0126] (5) Heat treatment: The prepared soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 485℃ and the solution time is 1.5h. The aging temperature is 150℃ and the aging time is 8h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0127] Example 6

[0128] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 4%, Cu 1.5%, Zr 0.25%, Ga 3%, In 1.5%, Sn 1.5%, Li 0.8%, V 0.05%, Hf 0.04%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0129] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0130] (1) Alloy smelting: Pure aluminum ingots are heated and melted under a nitrogen atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 760℃ for 15 min, degassed for 10 min, and then allowed to stand for 10 min after slag removal to obtain the melt.

[0131] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 130 mm / min.

[0132] (3) Homogenization treatment: The homogenization temperature is 470℃ and the homogenization time is 15h;

[0133] (4) Extrusion forming: The homogenized soluble aluminum alloy casting rod is hot-extruded. The extrusion barrel temperature is 420℃, the casting rod temperature is 480℃, the extrusion speed is 1.0mm / s, and the extrusion ratio is 25, to obtain... Soluble aluminum alloy extrusions;

[0134] (5) Heat treatment: The prepared soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 460℃ and the solution time is 2h. The aging temperature is 140℃ and the aging time is 15h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0135] Example 7

[0136] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 3%, Cu 0.8%, Zr 0.26%, Ga 3%, In 1%, Sn 1%, Li 1.5%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0137] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0138] (1) Alloy smelting: Pure aluminum ingots are heated and melted under a nitrogen atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 760℃ for 15 min, degassed for 15 min, and slag removed. After standing for 10 min, the melt is obtained.

[0139] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 130 mm / min.

[0140] (3) Homogenization treatment: The homogenization temperature is 450℃ and the homogenization time is 20h;

[0141] (4) Extrusion forming: The homogenized soluble aluminum alloy casting rod is hot-extruded. The extrusion barrel temperature is 420℃, the casting rod temperature is 470℃, the extrusion speed is 0.5mm / s, and the extrusion ratio is 35, to obtain... Soluble aluminum alloy extrusions;

[0142] (5) Heat treatment: The prepared soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 475℃ and the solution time is 1h. The aging temperature is 135℃ and the aging time is 18h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0143] Example 8

[0144] This embodiment provides a high-strength biodegradable aluminum alloy material, which, by weight percentage, consists of the following components: Zn 3%, Cu 0.5%, Zr 0.05%, Ga 4%, In 2%, Sn 4%, Li 1.2%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0145] The preparation method of the above-mentioned high-strength biodegradable aluminum alloy material is as follows:

[0146] (1) Alloy smelting: Pure aluminum ingots are heated and melted under an argon atmosphere to obtain aluminum liquid. Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added in proportion and smelted. After the alloy is completely melted, a refining agent (a mixture of KCl, NaCl, Na3AlF6 and Na2CO3 in equal mass ratio) is added. The mixture is refined at 760℃ for 20 min, degassed for 15 min, and then allowed to stand for 10 min after slag removal to obtain the melt.

[0147] (2) Alloy casting: The melt is continuously poured into the crystallizer of a semi-continuous casting machine to obtain a semi-continuous casting rod. The casting speed is 130 mm / min.

[0148] (3) Homogenization treatment: The homogenization temperature is 460℃ and the homogenization time is 12h;

[0149] (4) Extrusion forming: The homogenized soluble aluminum alloy casting rod is hot-extruded. The extrusion barrel temperature is 420℃, the casting rod temperature is 485℃, the extrusion speed is 0.8mm / s, and the extrusion ratio is 30, to obtain... Soluble aluminum alloy extrusions;

[0150] (5) Heat treatment: The prepared soluble aluminum alloy extrusion is subjected to solution treatment and aging treatment. The solution temperature is 500℃ and the solution time is 0.5h. The aging temperature is 150℃ and the aging time is 20h. It is then air-cooled to room temperature to obtain a high-strength biodegradable aluminum alloy material.

[0151] Comparative Example 1

[0152] This comparative example provides an aluminum alloy material, which, by weight percentage, consists of the following components: Zn 7%, Cu 1.2%, Zr 0.05%, Ga 0.1%, In 0.1%, Sn 0.1%, Li 0.3%, V 0.01%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0153] The preparation method of the aluminum alloy material is the same as that in Example 2.

[0154] Comparative Example 2

[0155] This comparative example provides an aluminum alloy material, which, by weight percentage, consists of the following components: Zn 5%, Cu 1.2%, Zr 0.1%, Ga 0.1%, In 0.1%, Sn 0.1%, Li 0.3%, V 0.02%, Hf 0.01%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0156] The preparation method of the aluminum alloy material is the same as that in Example 5.

[0157] Comparative Example 3

[0158] This comparative example provides an aluminum alloy material, which, by weight percentage, consists of the following components: Zn 4%, Cu 1.5%, Ga 1.5%, In 1.5%, Sn 1%, Li 1%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0159] The preparation method of the aluminum alloy material is the same as that in Example 6.

[0160] Comparative Example 4

[0161] This comparative example provides an aluminum alloy material, which, by weight percentage, consists of the following components: Zn 3%, Cu 1.5%, Ga 4%, In 1%, Sn 3%, Li 1%, with the balance being Al and unavoidable impurities, wherein the impurity content is ≤0.2%.

[0162] The preparation method of the aluminum alloy material is the same as that in Example 8.

[0163] Comparative Example 5

[0164] Same as Example 2, except that when preparing aluminum alloy materials, Ga, In, Sn and Li are replaced by Al by mass, that is, the addition of Ga, In, Sn and Li is omitted.

[0165] The preparation method is the same as in Example 2.

[0166] Comparative Example 6

[0167] Same as Example 2, except that V and Hf are not added when preparing aluminum alloy materials, that is, V and Hf are replaced by Al by mass.

[0168] The preparation method is the same as in Example 2.

[0169] Table 1. Test results of mechanical properties and solubility of soluble aluminum alloys in each embodiment and comparative example.

[0170]

[0171]

[0172] The test results show that:

[0173] The high-strength biodegradable aluminum alloy material prepared by the method of this invention has a tensile strength of up to 332 MPa and a yield strength of up to 264 MPa. Its dissolution rate at 90°C and 3 wt% KCl ranges from 120 to 195 mg / cm³. 2 / h, with good mechanical properties and biodegradability.

[0174] The Zn content significantly affects the microstructure and mechanical properties of aluminum alloys. Higher Zn content results in better mechanical and casting properties, but as the Zn content decreases, the alloy's strength drops significantly. This is likely because Zn refines the grain size, while lower Zn content leads to grain coarsening and reduced strength. Cu, as a strengthening element, improves alloy strength, but excessively low Cu content may prevent the formation of an effective Al₂Cu strengthening phase, resulting in decreased mechanical properties. A comparison of Example 1 with Comparative Examples 1-6 shows that the mechanical properties of the alloy decrease significantly when Zr, V, and Hf are not added. This indicates that the addition of Zr, V, and Hf to the aluminum matrix in a certain proportion provides synergistic strengthening, effectively improving the alloy's strength and stabilizing its mechanical properties. Furthermore, compared to Comparative Examples 1-5, Ga / In ratios less than 2 or greater than 3, and Sn / In ratios less than 1 or greater than 2, can all form brittle phases at grain boundaries, reducing the alloy's mechanical properties. Compared with Comparative Examples 1, 2 and 5, which did not contain low-melting-point metals, the addition of low-melting-point metals (Ga, In, Sn, Li) in Examples 1-8 forms a eutectic phase at the grain boundaries, lowers the local melting point and weakens the grain boundary structure, thereby providing favorable conditions for the dissolution of the alloy.

[0175] The high-strength biodegradable aluminum alloy material of the present invention simultaneously adds Zn, Cu, Zr, V and Hf to the alloy. Compared with comparative examples 3 and 4 without Zr, V and Hf, and comparative example 6 without V and Hf, the addition of Zr, V and Hf synergistically improves the mechanical properties of the alloy through multiple mechanisms such as grain refinement and dispersion strengthening. The comparative examples lack the strengthening effect of these elements and have poor performance.

[0176] In Example 1, the mass ratio of Ga to In was 2.25, and the mass ratio of Sn to In was 1.875; in Example 2, the mass ratio of Ga to In was 2.4, and the mass ratio of Sn to In was 2; in Example 3, the mass ratio of Ga to In was 2, and the mass ratio of Sn to In was 2; in Example 4, the mass ratio of Ga to In was 2.5, and the mass ratio of Sn to In was 1; in Example 5, the mass ratio of Ga to In was 3, and the mass ratio of Sn to In was 1.5; in Example 6, the mass ratio of Ga to In was 2, and the mass ratio of Sn to In was 1; in Example 7, the mass ratio of Ga to In was 3, and the mass ratio of Sn to In was 1.5; in Example 8, the mass ratio of Ga to In was 2, and the mass ratio of Sn to In was... The mass ratio of Ga to In in Comparative Example 1 was 2; the mass ratio of Ga to In in Comparative Example 2 was 1; the mass ratio of Sn to In in Comparative Example 3 was 1; the mass ratio of Sn to In in Comparative Example 4 was 4; and the mass ratio of Sn to In in Comparative Example 5 was 3. According to the data in Table 1, adding Ga, In, Sn, and Li during the preparation of the aluminum alloy, while ensuring that the mass ratio of Ga to In is 2–3 and the mass ratio of Sn to In is 1–2, effectively improves the dissolution rate of the aluminum alloy. The method of this invention can successfully prepare high-strength biodegradable aluminum alloy materials. Although Ga, In, Sn, and Li were added in Comparative Examples 1–4, the mass ratio of Ga to In was not 2–3, and the mass ratio of Sn to In was not 1–2, resulting in the prepared aluminum alloys lacking biodegradability. Furthermore, the contents of Zr, V, and Hf in Example 8 are basically taken as the lower limit of the scope of the present invention, and the value of the dissolution rate of aluminum alloy material is not significantly reduced. Therefore, the contents of Zr, V, and Hf will not affect the dissolution rate of alloy material.

[0177] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A high-strength degradable aluminum alloy material, characterized by, By weight percentage, comprising the following components: Zn 3.0-7.0%, Cu 0.5-1.5%, Zr 0.05-0.35%, Ga 0.1-4.0%, In 0.1-2.0%, Sn 0.1-4.0%, Li 0.001-1.5%, V 0.005-0.05%, Hf 0.005-0.05%, the balance of Al and inevitable impurities, wherein the impurity content ≤0.2%, and the mass ratio of Ga and In is 2-3, the mass ratio of Sn and In is 1-2.

2. The high-strength degradable aluminum alloy material of claim 1, wherein, By weight percentage, comprising the following components: Zn 5.0-7.0%, Cu 0.5-1.2%, Zr 0.2-0.3%, Ga 1.0-3.0%, In 0.4-1.0%, Sn 1.0-1.5%, Li 0.05-1.2%, V 0.01-0.05%, Hf 0.01-0.035%, the balance of Al and inevitable impurities, wherein the impurity content ≤0.2%, and the mass ratio of Ga and In is 2-3, the mass ratio of Sn and In is 1-2.

3. The high-strength degradable aluminum alloy material of claim 1, wherein, By weight percentage, comprising the following components: Zn 3.0-5.0%, Cu 1.0-1.5%, Zr 0.25-0.35%, Ga 2.5-4.0%, In 1.5-2.0%, Sn 1.5-4.0%, Li 0.8-1.5%, V 0.01-0.05%, Hf 0.01-0.035%, the balance of Al and inevitable impurities, wherein the impurity content ≤0.2%, and the mass ratio of Ga and In is 2-3, the mass ratio of Sn and In is 1-2.

4. A method of producing the high-strength degradable aluminum alloy material according to any one of claims 1 to 3, characterized by, Comprising the following steps: Under the protection of inert gas, a pure aluminum ingot is heated and melted to obtain an aluminum liquid, Zn, Cu, V, Zr, Hf, Ga, In, Sn and Li are added to the aluminum liquid and fully stirred, degassing after refining, standing, and casting into a semi-continuous casting rod; The semi-continuous casting rod is subjected to homogenization treatment; The semi-continuous casting rod after homogenization treatment is subjected to hot extrusion treatment to obtain a rod material; The rod material is subjected to heat treatment to obtain the high-strength degradable aluminum alloy material.

5. The method of producing a high-strength degradable aluminum alloy material according to claim 4, characterized by, The refining is refined at 750-780℃ for 10-30min; And / or, the degassing time is 10-20min; And / or, the standing time is 5-20min.

6. The method of producing a high-strength degradable aluminum alloy material according to claim 4, characterized by, The homogenization treatment temperature is 440-470℃, and the time is 10-20h.

7. The method of producing a high-strength degradable aluminum alloy material according to claim 4, characterized by, The hot extrusion treatment is: the extrusion cylinder temperature is 380-460℃, the casting rod temperature is 400-500℃, the extrusion speed is 0.4-1.5mm / s, and the extrusion ratio is 20-50.

8. The method of producing a high-strength degradable aluminum alloy material according to claim 4, characterized by, The heat treatment includes solid solution treatment and aging treatment.

9. The method of producing a high-strength degradable aluminum alloy material according to claim 8, characterized by, The solid solution treatment temperature is 450-500℃, and the solid solution treatment time is 0.5-2h; And / or, the aging treatment temperature is 100-150℃, and the aging treatment time is 8-20h.

10. Use of the high-strength degradable aluminum alloy material according to any one of claims 1 to 3 for the manufacture of unconventional natural gas production fracturing tools.

Citation Information

Patent Citations

  • High-ductility soluble aluminum alloy, preparation method and application

    CN114686734A

  • High-strength soluble magnesium alloy and preparation method thereof

    CN117660819B

  • Degradable thermosetting composite material with bicontinuous microstructure and degradable underground plugging tool prepared from degradable thermosetting composite material

    CN118834372A

  • High-elongation soluble aluminum alloy and preparation method and application thereof

    CN116005046A

  • Aluminum alloy capable of being rapidly dissolved in neutral medium as well as preparation method and application of aluminum alloy

    CN116005051A